De Vargas a Juscelino rupturas e continuidades no processo de desenvolvimento brasileiro (1951 61) - Mesquita, Priscila Alcântara Sena (2013)
The objective of this dissertation is to make an analysis of the second term of Getúlio Vargas and the government of Juscelino Kubitschek, highlighting points of rupture and continuity. The 1950s were very important for the Brazilian economic development process. It was a period of intense growth, maturing, and changes in the country. However, along with these transformations, inequalities arose and the political interests of each group in Brazilian society stood out. If, on one hand Vargas sought in his government development linked to economic stability by initiating the partnership with the North American government with the establishment of the Joint Brazil-United States Commission [Comissão Mista Brasil-Estados Unidos (CMBEU)] JK had the intention of promoting growth at any cost, based on these same projects generated by CMBEU. In this way, the search for consolidation of the national industry by Vargas, whether with internal or external resources, was later weakened due to the intense flow of foreign capital observed during Kubitschek s government. Within this context, the economic imbalance became increasingly greater, but as it had been accompanied by economic growth, it was seldom discussed by the society of the time. Thus, the problems generated by inflation and external imbalance, resulting from this disorderly growth, brought problems for the successors of JK and, further on, compromised the Brazilian democracy itself